How to Know a Citizen When You See One? The Sex of a Citizen - Zaharijević, Adriana (Identities: Journal for Politics, Gender and Culture, 2013)
The paper explores how the 19th century scientific discourses naturalized sex. Those highest ranking forms of public knowledge are situated within a broader context of knowledge production on what it is to be human and how the gradation of humanity has been made possible. The paper concentrates on the sexed ‘humans’ in order to show how sex worked as the political and epistemic tool which foreclosed the domains of citizenship for women. I argue that epistemic incomprehensibility is fundamentally related to the politically liminal or impossible lives. Thus, by using examples from the Victorian sciences, the paper shows how the scientific naturalization of sex actively limited the space of citizenship for women. Author(s): Adriana Zaharijević Title (English): How to Know a Citizen When You See One? The Sex of a Citizen Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 71-82 Page Count: 11 Citation (English): Adriana Zaharijević, “How to Know a Citizen When You See One? The Sex of a Citizen,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 71-82.